Usability Testing Website Dengan Menggunakan Metode System Usability Scale (Sus)s - Welda, Welda; Putra, Desak Made Dwi Utami; Dirgayusari, Ayu Manik (International Journal of Natural Science and Engineering, 2020)
In ensuring the effectiveness, efficiency and user satisfaction of the website, it is necessary to evaluate and evaluate the website.  This study aims to analyze the Usability Testing Website Using the System Usability Scale (SUS) Method.  The method used in this study is the SUS (System Usability Scale).  Data collection techniques in this study were interview techniques, observation techniques or questionnaire techniques.  The instrument used in this study was a questionnaire.  The subjects in this study consisted of 30 respondents.  The data analysis technique used in this research is descriptive qualitative analysis.  The results of the evaluation in this study, namely the results of the assessment of the respondents, obtained a total value of the SUS score of 2012.50 with the resulting average value of 67.08, this shows that the total SUS score on the STIKI Indonesia website is 67.08, which means the level of user Acceptability Range  is Marginal High, Grade Scale level is category D, user Adjective Rating level is OK category and SUS Score Percentile Rank is grade D. The website still needs to be evaluated and developed further so that its use can be more optimal.